Comparative Analysis Of The Economic Burden Of Tuberculosis Patients With And Without HIV In Kupang City - Krisandy Surya Wibawa; Ika Febianti Buntoro; Nimas Prita Rahajengningtyas Kusuma Wardani; Sangguana Marthen Jacobus Koamesah (CV. AFDIFAL MAJU BERKAH, 2026)
Tuberculosis (TB) is a public health problem that imposes a substantial economic burden, particularly among patients with Human Immunodeficiency Virus (HIV) coinfection. This study aimed to analyze the differences in economic burden between TB patients with HIV and TB patients without HIV in Kupang City. This study employed an analytic observational design with a case–control approach. A total of 64 respondents were included, consisting of 34 TB–HIV patients as the case group and 34 TB patients without HIV as the control group, selected through purposive sampling based on inclusion and exclusion criteria. The economic burden analyzed included direct non-medical costs, indirect costs, and the occurrence of catastrophic costs. The results showed differences in the total economic burden between TB patients and TB–HIV patients in Kupang City. TB–HIV patients tended to bear a higher economic burden than TB patients without HIV. These differences were mainly driven by higher direct non-medical costs and indirect costs, particularly income loss, asset sales, and indebtedness during the treatment period. In addition, the proportion of patients experiencing catastrophic costs was higher in the TB–HIV group than in the TB group. The study demonstrated a statistically significant difference in the total economic burden between the two groups. The median direct non-medical cost among TB–HIV patients was IDR 113,500.00, which was higher than that among TB patients without HIV (IDR 17,500.00; p < 0.001). The median indirect cost among TB–HIV patients was IDR 2,450,000.00, whereas it was IDR 0.00 among TB patients without HIV (p < 0.001). A total of 23.5% of TB–HIV patients experienced catastrophic costs, while none were observed among TB patients without HIV, with a significant association between HIV status and the occurrence of catastrophic costs (p < 0.003).